Anesthetic management in a pediatric patient with primary extranodal sinus histiocytosis of the trachea, assisted by extracorporeal membrane oxygenation: a case report - Yamunaqué-Gonzáles, Claudia (2023)
The management of anesthesia in airway surgeries presents a significant challenge for the pediatric anesthesiologist. Tracheal stenosis, characterized by a decrease in tracheal lumen, can have various etiologies, with intubation being one of the most common, responsible for 20% of cases and generating severe symptoms in 1% of patients. Among the rarest etiologies is extranodal sinus histiocytosis of tracheal origin. In this report, we present the case of a 13-year-old patient with an intrathoracic mass that obstructed 40% of the tracheal lumen, endangering his life. The management of this case involved intubation, the use of difficult airway devices, total intravenous anesthesia, and extracorporeal membrane oxygenation. These techniques are viable alternatives for the management of complex tracheal pathologies, providing a wide safety margin for pediatric patients. This case underscores the importance of appropriate selection of anesthetic techniques in cases of tracheal stenosis of rare etiology.